Effect of business social responsibility (BSR) on performance of SMEs in Nigeria - Gorondutse, Abdulahi Hassan (2014)
The objective of this study is to examine the effects of Business Social Responsibilities (BSR) on performance of SMEs in Nigeria. Additionally, this study also examines the mediation effect of organizational culture on the relationship between BSR and performance. BSR constructs are commitment, trust, perceived ethics, organizational culture and performance. A conceptual framework was developed based on extant literatures and the develop model is based on these BSR constructs Data was collected through hand delivery method by sending questionnaires to 800 SMEs managers/owners. This study used purposive sampling for sample selection. Partial Least Squares (PLS) algorithm and bootstrap techniques were used to test the study‘s hypotheses. The results provide support for most of the hypothesized relationships for the study. Specifically, commitment, trust, perceived ethics, and organizational culture are significantly and positively related to performance. On the other hand, commitment is significantly and negatively related to performance. Additionally, commitment, trust, and perceived ethics are significantly and positively related to organizational culture. Furthermore, the results of mediation indicate that all the three hypotheses are significant. Therefore, significant positive effects of commitment, trust, and perceived ethics suggest that the variables are important in relation to performance. The outcome of this study provides significant contributions to both managers and researchers for further understanding on the effect of BSR and organizational culture on performance. As such, organizations should be encouraged to exhibit these social responsibilities for better performance. Improved performance of organizations can advance the social responsibility practices in organizations. Contributions, limitations, implications and necessary suggestions on the new areas of research are recommended and discussed in this research.